Ovine and Caprine Brucellosis (Brucella melitensis) in Aborted Animals in Jordanian Sheep and Goat Flocks - Assadullah Samadi; M. MK. Ababneh; N. D. Giadinis; S. Q. Lafi (Veterinary Medicine International)
Two hundred and fifty five biological samples were collected from 188 animals (81 sheep and 107 goats) during the lambing season from September 2009 to April 2010 from the Mafraq region of Jordan. Sampled animals belonged to 93 sheep and goat flocks that had abortion cases in the region. One hundred and seven (41.9%) biological samples were positive for the omp2 primers that were able to identify all Brucella species in the collected samples which were obtained from 86 aborted animals (86/188=45.7%). Using the B. melitensis insertion sequence 711 (IS711) primers on the 107 omp2 positive samples, only 61 confirmed to be positive for B. melitensis. These positive samples were obtained from 28 sheep and 33 goats. The prevalence rate of B. melitensis was 27.1% (51/188) among aborted animals. For differentiation between vaccine strain and field strain infection, polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method using PstI endonuclease enzyme was used. Vaccination with Rev-1 in the last year (OR=2.92, CI: 1.1–7.7) and grazing at common pasture (OR=2.78, CI: 1.05–7.36) were statistically significant (P≤.05) risk factors positively associated with the occurrence of brucellosis in sheep and goat flocks.